Cascaded singlemode-multimode-singlemode fiber structure for directional bending sensing - Wang, Yu (2018)
In this dissertation, a cascaded inline fiber Mach-Zehnder interferometer (CMZI) with Vernier effect is proposed and demonstrated for directional curvature sensmg. The device consists of two cascaded singlemode-multimode-singlemode (CSMS) fiber structures formed by core-offset splicing technique. Because of the mode field mismatch and the offset between multimode fiber (MMF) and singlemode fiber (SMF), modes in SMF can be guided in core, cladding and air surface ofthe SMF. The multi modes in the SMF concurrently propagates and interferes, resulting interference spectrum. Particularly, two such SMS fiber structure are cascaded to generate the Vernier effect to amplify sensitivity. When the CSMS fiber structure is bent, the optical path difference will be changed, causing the resonant wavelength of the Vernier spectrum to shift. Exceptionally, since the bending sensitivity is different under different bending direction, different bending direction range from 0° to 360° can thus be measured by monitoring the bending se nsitivity. Theoretical analyses are conducted to thoroughly explain the working principle of the CSMS fiber structure. Vernier effect is also generalized to conclude more than two frequency components for analysis. Then, a CSMS fiber is elaborately fabricated for experimental demonstration. Experimental results show that the proposed CSMS fiber structure has a bending sensitivity as high as 13. 52nm/m-1. When the curvature is fixed, the CSMS structure can be employed to measure bending direction. The bending direction sensitivity reaches 410pm/degree within the rotation angle from 130° to 200°. The effect of temperature on the response of the curvature sensor is also experimentally investigated. Key words : optical fiber sensor, Mach-Zehnder interferometer, curvature, bending direction, generalized Vernier effect